Teachers and Their Role in Ensuring Quality Education: An Islamic Philosophical Perspective (Philosophy and Progress, 2025)
This paper addresses the gap between material and moral education by exploring the role of teachers in ensuring quality education from an Islamic philosophical perspective. The study investigates how Islamic principles of Towhid (oneness of God), Amanah (divine trust), and the integration of Naqli (revealed) and Aqli (rational) knowledge can guide teachers in nurturing intellectually, morally, and spiritually balanced individuals. It also puts specific focus on the concept of Hikmah (spiritual wisdom) as derived from internal Islamic sources. Employing a qualitative methodology, the research draws on Qur’anic verses, Hadith, and works of classical Islamic scholars like Al-Ghazali, Ibn Sina, and Al-Farabi to conceptualize the teacher’s multifaceted role. Finally, I argue that teachers are not merely transmitters of knowledge, but ethical guides, social reformers, and agents of Hikmah. Integrating these insights into contemporary education systems can enrich moral foundations and foster holistic human development.Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 125-144